Using Constant Time Delay to Teach Braille and the Nemeth Code for Mathematics and Science Notation to Students Making the Transition from Print to Braille. (September 2015) - Ivy, Sarah E.; Hooper, Jonathan D.
Introduction: Many students with adventitious vision loss or progressive vision loss need to transition from print to braille as a primary literacy medium. It is important that this transition is handled efficiently so that the student can have continued access to a literacy medium and make progress in the core curriculum. For this study, we used constant time delay to teach literary braille contractions and Nemeth Code for Mathematics and Science Notation (hereafter, Nemeth Code) braille symbols to learners with visual impairments who were making the transition from print to braille. Methods: A single-subject, multiple-probe research design was used to test the effectiveness and efficiency of constant time delay to teach literary braille or Nemeth Code. Three female students, aged 13 to 15 years, participated at a specialized school for students with visual impairments. The students' braille and math instructor delivered interventions in the classroom. Procedural fidelity and interobserver agreement data were collected. Results: Two students each learned 40 short-form literary braille contractions, and one student learned 28 Nemeth Code symbols throughout the study. Students appeared to generalize learning after instruction with the first word set to identify similar contractions. Students maintained learning throughout the study at high levels. Visual analysis of the data suggests a functional relationship between constant time delay and contraction identification. Discussion: This study replicated previous work (Hooper, Ivy, & Hatton, 2014) to expand understanding of the scope of the usefulness of time delay in braille education. Implications for practitioners: For students making the transition from print to braille, constant time delay may be an efficient method to help students acquire braille. The efficiency itself may increase students' confidence and motivation to learn braille.